Endoscopic full-thickness resection of the stomach: an experimental approach - Kähler, Georg; Langner, C.; Suchan, K. L.; Freudenberg, S.; Post, Stefan (Surgical endoscopy and other interventional techniques, 2006)
Endoluminal endoscopic resections of the gastrointestinal (GI) tract have had increasing significance in recent years. Except for the extraperitoneal part of the rectum, endoscopic resections are restricted to the mucosal and submucosal layer to preserve the integrity of the GI tract wall.
Gesehen am 30.05.2022